Economic impact of extending reflexed cryptococcal antigenaemia CD4 threshold in South Africa - Naseem Cassim; Lindi-Marie Coetzee; Manuel P. da Silva; Deborah K. Glencross; Wendy S. Stevens (AOSIS, 2024)
Background: Reflexed cryptococcal antigenaemia (CrAg) testing has been offered since 2016 in South Africa, on remnant CD4 specimens, for people with a count 100 cells/μL. Local guidelines recommended extending testing to 200 cells/μL. Objectives: This study assessed the cost per result and annual equivalent costs (AEC) for CD4 counts 100 cells/μL and 100 to 200 cells/μL, as well as determining the cost to find one CrAg-positive case. Method: An ingredients-based costing was used to determine the cost per result. The CrAg detection rate for 100 cells/μL was obtained from operational reports of 2019. For 100 cells/μL to 200 cells/μL, a CrAg detection rate of 2% was assumed. One-way sensitivity analysis determined the impact of varying CrAg detection rates on the cost to find one case. Local data from the Western Cape province, which offers testing for counts of 100 cells/μL to 200 cells/μL, from September 2022 to January 2023, were interrogated to establish detection rates. Results: There were 283 240 (AEC: $1 670 370) specimens with counts of 100 cells/μL and 300 624 (AEC: $1 772 890) with counts of 100 cells/μL to 200 cells/μL. A cost per result of $5.897 was reported. The cost to find one CrAg case ranged from $589.74 to $73.72 for a detection rate of 1% to 8%. Local data for a count of 100 cells/μL to 200 cells/μL revealed a CrAg detection rate of 1.6%. Conclusion: The study findings reveal that extending reflexed CrAg testing to 200 cells/μL would double test volumes with fewer positive cases reported for those with a count of 100 cells/μL to 200 cells/μL.